1982
DOI: 10.2337/diab.31.5.388
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diabetes Mellitus on Sterol Synthesis in the Intact Rat

Abstract: Diabetes mellitus in both humans and animals is characterized by elevations in plasma cholesterol concentrations. The cause of this hypercholesterolemia is unknown. The present study employed tritiated water to quantity sterol synthesis in intact diabetic and control animals. Sterologenesis was 60-246% greater in the gut of diabetic animals than in controls. This enhancement of sterol synthesis occurred soon after the onset of diabetes and persisted for at least 3 wk. Moreover, insulin therapy markedly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…Over 6 h, a large fraction of the sterols synthesized in the liver is transported to peripheral tissues. This explains the apparently low contribution of the liver to total-body sterol synthesis reported by Feingold et al (26). Our data from control rats are very similar to those of Jeske and Dietschy (27) and Lakshmanan and Veech (28), who killed their animals 1 and 2 h, respectively, after injection of 3 H 2 O.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Over 6 h, a large fraction of the sterols synthesized in the liver is transported to peripheral tissues. This explains the apparently low contribution of the liver to total-body sterol synthesis reported by Feingold et al (26). Our data from control rats are very similar to those of Jeske and Dietschy (27) and Lakshmanan and Veech (28), who killed their animals 1 and 2 h, respectively, after injection of 3 H 2 O.…”
Section: Discussionsupporting
confidence: 90%
“…Our in vivo data on sterol synthesis in diabetic rats (Table 3) are similar to those of Young et al (25) but are very different from those of Feingold et al (26), who reported that the rate of cholesterol synthesis is unchanged in the liver and increased by 26% in the total body of diabetic compared with control rats. The contribution of the liver to total cholesterol synthesis was 29 and 24% in control and diabetic rats, respectively.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The inability of the diabetic rat jejunal EMM to cope with an increased dietary load of cholesterol may be related to the known changes in cholesterol metabolism that are observed in diabetes. Intestinal de novo synthesis of cholesterol has been shown to be increased 2-3-fold in streptozotocin-diabetic rats (40) associated with an increase in 3-hydroxy-3-methylglutaryl-CoA reductase activity (41)(42)(43). Cholesterol feeding did not alter cholesterol synthesis in control animals, but markedly inhibited cholesterol synthesis in the diabetic small intestine (44).…”
Section: Discussionmentioning
confidence: 99%
“…Serum cholesterol and HDL-cholesterol concentrations were increased in these insulin overtreated animals, perhaps as a result of increased food intake. Gut cholesterol synthesis is increased in insulinopenic streptozotocin diabetic rats, and might be expected to be normal or reduced in our over-treated animals [26].…”
Section: Discussionmentioning
confidence: 85%